2017
DOI: 10.2147/ppa.s124605
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence in patients with type 2 diabetes mellitus correlates with different coping styles, low perception of self-influence on disease, and depressive symptoms

Abstract: BackgroundInsulin analogs are regarded as more convenient to use than human insulin; however, they require a different administration scheme due to their unique pharmacokinetic and pharmacodynamic properties. This study aimed to assess difficulties with adherence to treatment with insulin analogs in patients with type 2 diabetes mellitus (T2DM), who had previously been treated with human insulin. The associations between difficulties with adherence and clinical, demographic, and psychological characteristics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…In our study, the highest percentages of non-adherence occurred when the patient took four or more tablets daily (OR = 1.6). Controversy exists regarding the association between age and treatment adherence [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Some studies have found greater non-adherence in older patients due to forgetfulness, although others have failed to find this association [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the highest percentages of non-adherence occurred when the patient took four or more tablets daily (OR = 1.6). Controversy exists regarding the association between age and treatment adherence [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Some studies have found greater non-adherence in older patients due to forgetfulness, although others have failed to find this association [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the individualized analysis of each of these variables, based on their measures of association according to the odds ratios obtained (Table 1), we will be able to design strategies focused on reducing non-adherence in these complex patients to improve control of their chronic diseases. Examination of other studies found no consistency regarding the relationship between non-adherence and dependent socioeconomic, demographic and work-family factors [5][6][7][8][9][10][11][12][13][14][15][16], although all the authors agree that non-adherence is associated with greater therapeutic complexity and a poorer doctor-patient relationship [17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro fator associado à baixa adesão pode ser o baixo nível de escolaridade 22,23 . Dado que se assemelha com o presente estudo, pois pacientes do grupo sem adesão à fonoterapia na área de voz possuem menores níveis educacionais em relação a pacientes com adesão ao tratamento proposto, mesmo sem diferenciação estatística entre os grupos quanto ao grau de instrução.…”
Section: Discussionunclassified
“…Karlsen, Oftedal and Bru (2012) found that 86% and 78% of patients reported occasionally or frequently using active coping and planning. A different results were concluded in a study on patients with Type 2 diabetes (Kokoszka, 2017) where patients used undifferentiated coping strategies, which means a combination of task-oriented, best solution-oriented, emotion-oriented and avoidance coping.…”
Section: Coping Strategies Employed By Patients Diagnosed With T2dmmentioning
confidence: 96%